Asuhan Keperawatan Pada Anak Dengan Bronkopneumonia - Indri Damayanti; Siti Nurhayati (AKPER Pasar Rebo, 2019)
Bronchopneumonia is a type of pneumonia which affects one or several lung lobes which are marked by the presence of infiltrates caused by bacteria, viruses, fungi, and odd object. Children with bronchopneumonia are usually characterized by symptoms of fever, tachypnea, productive cough, decreased appetite, decreased breath sounds, nasal lobe breath, chest wall retraction and lethargy. The impact that will occur on children with bronchopneumonia is OMA, atelectasis, pleural effusion, emphysema and meningitis. The purpose of writing is that students are expected to be able to provide nursing care to children with bronchopneumonia. Writing method is descriptive or description of a case. The results of scientific papers obtained by An. F with bronchopneumonia with signs and symptoms of fever, productive cough and sound ronchi in the right lung. Nursing problems at An.F are: ineffective airway clearance, risk of nutritional deficits, risk of hypovolemia, knowledge deficit and risk of infection. After three days of implementation, it was found that two problems were resolved and three that had not been resolved were ineffective airway clearance, risk of hypovolemia and risk of infection.